EMBEDDED SEX EDUCATION IN PESANTREN: STUDENTS’ MEANING-MAKING AND PEDAGOGICAL IMPLICATIONS - Mainuddin,; Syamsul Arifin,; M. Nurul Humaidi,; Romelah,; Saiful Anwar, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This study examines how students interpret sex education integrated into pesantren learning and its pedagogical implications for the learning process at Pondok Pesantren NH West. This study uses a qualitative case study design. Data were collected through in-depth interviews with six students, observations, and documentation, and analyzed using thematic analysis. The findings show that students generally do not know the formal term “sex education” or tarbiyah jinsiyyah, but understand the substance of the material through learning of Islamic jurisprudence (fiqh), manners (adab), pesantren rules, and biological material related to reproduction. For students, sex education is understood as a moral guideline for maintaining awrah (parts of the body that should be covered according to Islamic teachings), personal hygiene, honor, and social boundaries, as well as practical knowledge relevant to daily life in the pesantren environment. Analysis through Piaget's theory of cognitive development and Bandura’s social cognitive theory shows that the effectiveness of sex education in pesantren is formed by two interrelated processes, namely the cognitive assimilation of material into the religious scheme that students already have and social strengthening through teacher example, discipline, supervision, and habituation in boarding life. The findings also show that student admissions are conditional: material is more readily accepted when framed in familiar moral-religious language, but learning comfort decreases when topics are conveyed too directly and through dominant lecture methods. This study concludes that the formalization of terms does not determine sex education in pesantren, but rather that it is determined by the integration of substance, religious framing, daily relevance, and pedagogical strategies. On that basis, this study offers the Pesantren-Embedded Sexuality Acculturation and Normative Learning Framework as a conceptual contribution to understanding value-based sex education in Pesantren.